iPhone application for shopping and dining loyalty membership - Chew, Andy Hesheng. (2012)
Most people hold more than 1 membership card in their wallet and to save the space inside the wallet, we would not bring all the membership out to shopping or dining. We would only bring what is necessary for day to day lives and sometime when we are at a particular shop, we would realise that we need those card that are placed at home. One thing for sure is everyone would bring their mobile as and when they go.